Effects of parity on preterm delivery in twin gestations conceived with in vitro fertilization - Michael S. Awadalla, M.D; Wael H. Salem, M.D; Jacqueline R. Ho, M.D; Victoria K. Cortessis, Ph.D; Ali Ahmady, Ph.D; Richard J. Paulson, M.D., M.S (Elsevier, 2023)
Objective: To determine the relationship between prior obstetrical history and gestational age at delivery in a twin pregnancy. Design: Retrospective cohort study using the United States Society for Assisted Reproductive Technology Clinic Outcomes Reporting System database. Setting: Clinic-based data. Patient(s): Patients undergoing in vitro fertilization (IVF) in the United States with live delivery of twins. Intervention(s): None. Main outcome measure(s): The main outcome measures are median gestational age at delivery and rate of preterm delivery (before 37 weeks). Result(s): The median gestational age at delivery of IVF-conceived twins was 36.3 (interquartile rate 34.4, 37.6) weeks for nulliparous women, 35.9 (34.0, 37.1) weeks for parous women with a prior preterm birth, and 36.7 (35.1, 37.7) weeks for parous women without a prior preterm birth. The rate of preterm delivery was 61% for nulliparous women, 70% for parous women with a prior preterm birth, and 55% for parous women without a prior preterm birth. Conclusion(s): Parous women without a history of preterm delivery had lower rates of preterm delivery in a subsequent twin pregnancy than nulliparous women. Nulliparous women had lower rates of preterm delivery compared with parous women with a history of preterm delivery.